The infinite sea - Yancey, Rick (Penguin Books, 2014)
The hugely anticipated second book in in the phenomenal new series that began with The 5th Wave - from Carnegie-shortlisted Rick Yancey. For Cassie Sullivan and the rest of Earth's remaining human survivors, the situation was already desperate when the 5th Wave hit. It's about to get worse.